Pengaruh Video Animasi Terhadap Pengetahuan Tentang ISPA pada Anak Sekolah Dasar Negeri Bangetayu Wetan 02 - Shabrina Cahya Amalina; Indra Tri Astuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Whe.n it come.s to kids, ARI can stop the.m from le.arning ne.w things, and to le.arn ne.w things, you ne.e.d e.ffe.ctive. ways to le.arn. The. goal of this study is to find out how animate.d vide.o me.dia affe.ct what e.le.me.ntary school kids in Se.marang know about the. IRA. The. re.se.arch me.thod use.d was quantitative., with a quasi-e.xpe.rime.ntal de.sign and a control group that wasn't the. same.. All of the. stude.nts at SDN Bange.tayu We.tan 02 are. part of the. study's population. Te.e.nage.rs de. 10 años a 12 años forman parte. de. la inve.stigación. E.l núme.ro de. e.studiante.s e.s de. 38, y fue. e.le.ccionada utilizando la técnica de. mue.stre.o inte.ncionado. It was a knowle.dge.-base.d que.stionaire. that was use.d as a tool in this study. The. te.aching me.thod use.d with animate.d movie.s and Powe.rPoint. For paire.d data, the. Wilcoxon te.st was use.d, and the. U-te.st from Mann-Whitne.y was use.d to se.e. if the.re. was a diffe.re.nce. in the. point score.s be.twe.e.n the. inte.rve.ntion group and the. control group. The. study's re.sults show that the. Wilcoxon te.st adde.d a value. (p = 0.000) to the. group that re.ce.ive.d the. inte.rve.ntion, but not to the. group that re.ce.ive.d the. control. This me.ans that both groups, the. inte.rve.ntion and control, le.arne.d more.. The. Mann-Whitne.y te.st also showe.d a significant diffe.re.nce. be.twe.e.n the. inte.rve.ntion and control groups, with a value. of (p = 0.000). If you want to improve. your knowle.dge., e.ducational films with animations are. a be.tte.r way to do it than Powe.rPoint pre.se.ntations.